RELEVANSI MATERI DAN METODE DALAM PROSES PEMBELAJARAN KEWIRAUSAHAAN PADA TINGKAT PENDIDIKAN TINGGI - Sulastri, Sulastri; Wahab, Zakaria; Sununianti, Vieronica Varbi (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 11 Nomor 1 Tahun 2017DO - 10.24843/MATRIK:JMBK.2017.V11.i01.p03, 2017)
ABSTRACT   Entrepreneurship program has become a national policy that is believed to be a tool to reduce unemployment and poverty. Therefore, entrepreneurship has become a national curriculum in almost every study program and has incorporated entrepreneurship module as one of the subjects in achieving learning outcome and graduate profile. The terms in entrepreneurship are also growing, with the aim of establishing a social construction towards the understanding of entrepreneurship as a science, which contains elements of knowledge, skills and attitudes. Besides, entrepreneurship construct that need to be built in the learning process is very complex and involves multiple disciplines, so it is important to study empirically the relevancy between learning materials and methods in entrepreneurship learning process in higher education. This study aims to examine whether there are differences in the learning materials and methods in entrepreneurial learning at higher education level. The research is carried out in several public and private universities with a sample of 304 students from some courses both for the field of sciences and social studies that have entrepreneurship as one of their taught modules. It can be concluded that entrepreneurial learning materials can be grouped in the aspect of (1) knowledge; (2) skills and (3) attitude. In each aspect, the learning materials are collected and grouped and observed on itslearning methodology. The results by using Anova testing show that there are differences in some teaching materials and learning methods in the same faculty or inter- faculty at several universities. Furthermore, in the cognitive construction of the entrepreneurship metaphor (innovation, creative, proactive and risk -taking), it is found that it has not been delivered usingrelevant learning methods, as well as learning models of personal development.
Keywords: Teaching materials , Methods of learning , Entrepreneurship